Strength ball training - Goldenberg, Lorne 1962-; Twist, Peter 1963- (Human Kinetics, 2016)
Medicine ball exercises are essential to developing core power, strength, balance, coordination and stability. Strength Ball Training presents those exercises along with instruction and advice on achieving results. Inside you will find assessments to help you determine your current ability level and corrective exercises that address deficiencies